(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Recognition and motivation are two important factors that can significantly affect the performance of teaching personnel. This study aims to explore the effects of recognition and motivation on teaching personnel in terms of their loyalty, commitment to work, and overall performance. Recognition and motivation are crucial aspects of organizational success. Recognizing and awarding the teaching personnel for their hard work, dedication, and achievements can improve overall performance. Motivated teaching personnel are more productive, engaged, and committed to their work, resulting in higher levels of motivation. The result shows the findings of the study. The three variables in the part of effects of recognition are all interpreted as highly motivated with their respective overall weighted means of performance (3.63), engagement (3.72), and commitment (3.65). The effects of recognition on motivation also show that in terms of loyalty (3.48), productivity (3.73), and responsibility (3.73), their respective overall weighted means are all interpreted as highly motivated. The study shows that most of the respondents are within the age range of 41 years old and above, are female, and are currently employed full-time. The majority of them have 4-6 years of teaching experience in BCP, and most of them are from BSBA and BSEntrep. It also reveals that there is no significant relationship between the effects of recognition in terms of performance, engagement, and commitment and the effects of recognition on motivation in terms of loyalty, productivity, and responsibility of teaching personnel. The researchers also suggested prioritizing the teaching personnel engagement, promoting per-department recognition at the end of the semester, and recognizing work anniversary dates. At the end of the study, the researchers crafted guidelines to enhance the recognition of the school and improve the motivation of the teaching personnel.